Institutionalizing East Asia mapping and reconfiguring regional cooperation - Ba, Alice D.; Kuik, Cheng-Chwee; Sudō, Sueo (Politics in Asia, 2016)
Institutional activities have remarkably transformed East Asia, a region once known for the absence of regionalism and regime-building efforts. Yet the dynamics of this Asian institutionalization have remained an understudied area of research. This book offers one of the first scholarly attempts to clarify what constitutes institutionalization in East Asia and to systematically trace the origins, discern the features, and analyze the prospects of ongoing institutionalization processes in the world's most dynamic region.